Development of Multicultural Instruments for Elementary School Teachers in Arts, Culture and Crafts Learning: Instrument Validation Analysis - Al Fajar, Beny; Kartika Sari, Intan; Rizka, Mifta; Rahman, Fadhila; Desmita, Izza; Balqis, Assyuqia; Zufriady; Radini (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to analyze the validity of the instrument and the readiness of elementary school teachers in implementing multicultural-based learning in the Arts, Culture, and Crafts (SBdP) subject. The research instrument consisted of a questionnaire and interview guide covering ten main indicators. The results of the validity test showed that all statement items were valid, so the instrument was suitable for use. The indicator with the highest achievement was the learning approach aspect (0.938–0.950), which confirmed the tendency of teachers to use thematic, contextual, humanist, and constructivist approaches. Conversely, the lowest achievement was found in the inclusive attitude indicator (0.533) and the use of local media (0.533), which indicated the need for improvement in both aspects. The interview results showed that teacher readiness in multicultural-based learning was in the high to very high category. Learning methods (82.6) and evaluation (82.6) were the dominant aspects, indicating teachers' ability to apply a variety of methods and fair assessment of cross-cultural artworks. Teachers' inclusive attitudes were also recorded as very high (82). However, the indicators in learning (62.7) and approaches (60.5) were still in the fairly high category. Overall, this study confirms that teachers are well prepared to support multicultural-based Arts and Culture learning, although strengthening is still needed in the aspects of approach and cultural integration so that its implementation is more comprehensive.